PPARs Integrate the Mammalian Clock and Energy Metabolism - Lihong Chen; Guangrui Yang (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) are a group of nuclear receptors that function as transcription factors regulating the expression of numerous target genes. PPARs play an essential role in various physiological and pathological processes, especially in energy metabolism. It has long been known that metabolism and circadian clocks are tightly intertwined. However, the mechanism of how they influence each other is not fully understood. Recently, all three PPAR isoforms were found to be rhythmically expressed in given mouse tissues. Among them, PPARα and PPARγ are direct regulators of core clock components, Bmal1 and Rev-erbα, and, conversely, PPARα is also a direct Bmal1 target gene. More importantly, recent studies using knockout mice revealed that all PPARs exert given functions in a circadian manner. These findings demonstrated a novel role of PPARs as regulators in correlating circadian rhythm and metabolism. In this review, we summarize advances in our understanding of PPARs in circadian regulation.